Fitting a Bivariate Distribution to Diameter-height Data of Forest Trees - Tewari, V. P.; Gadow, K. V. (Indian Forester, 1997)
Johnson's SB distribution has been used with good results to fit diameter and height data (Hafley and Schreuder 1977; Gadow, 1987). In the present paper the bivariate SBB distribution model was fitted to the diameter and height data of a stand of Acacia tortilis trees. The result shows that the predicted and observed frequencies are almost identical in the main part of the data range, thus confirming earlier observations of the suitability of the SBB for modelling the relationship between tree diameters and heights.